Sepsis research in Canada: An environmental scan of sepsis investigators, research, and funding. - Muhadisa Ali; Saad Y Salim; Fatima Sheikh; Alison E Fox-Robichaud; Sepsis Canada (PLOS Global Public Health)
Sepsis is the world's second leading cause of mortality. In 2017, the World Health Assembly declared sepsis a global priority and adopted a resolution prompting member states to improve the prevention, recognition, and management of sepsis. This cross-sectional study examines the sepsis research landscape in Canada, including demographics, scope, and funding. Using convenient sampling, sepsis researchers in Canada were asked to complete an online 20-question survey. We also scanned the CIHR funding database from 2012-2022 to quantify national research dollars spent on sepsis-related projects. Quantitative data was summarized using descriptive statistics, and textual descriptions of current sepsis research activities were analyzed thematically. With a response rate of 46% (69 of the 150), respondents were primarily men (n = 46/69, 67%), who identified as White/European (n = 49/69, 71%), and were professors or clinical professors (n = 36/69, 52%). The predominant areas of research focus were identification of sepsis (n = 21/55, 38%) and treatment/management (29/55, 53%) of sepsis, while sepsis prevention (n = 4/55, 7%) and sepsis education (n = 5/55, 9%) garnered less attention. Past 10 years of CIHR funding data revealed that only 0.7% ($85 million) of total funding ($11 billion) was towards sepsis research, of which only 2 were new-investigator awards. This study illustrates the need for improving the diversity of sepsis researchers in Canada; expanding the scope of research to address sepsis prevention, recovery, and education; and increasing overall funding to sepsis.